Influence of estrogen deficiency and its treatment with alendronate and estrogen on bone density around osseointegrated implants: radiographic study in female rats - Giro, Gabriela [UNESP]; Goncalves, Daniela [UNESP]; Sakakura, Celso Eduardo; Rodrigues Pereira, Rosa Maria; Marcantonio, Elcio [UNESP]; Orrico, Silvana Regina Perez [UNESP] (Mosby-elsevier, 2008)
Objective. This study evaluated the influence of estrogen deficiency and its treatment on bone density around integrated implants.Study design. Implants were placed in female rat tibiae. The animals were assigned to 5 groups: control, sham, ovariectomy, estrogen, and alendronate. The control group was humanely killed to confirm integration of the implant. The others were submitted to ovariectomy or sham surgery. Bone density was measured by digital radiographs at 6 points on sides of the implant.Results. The analysis of radiographic bone density revealed estrogen privation had a negative impact only in the cancellous bone. The estrogen group differed significantly ( P <.05) from the ovariectomy and alendronate groups. The alendronate group presented the highest density for all evaluated regions.Conclusion. Ovariectomy caused a decrease in the radiographic bone density in the cancellous region. Estrogen replacement therapy and alendronate were effective treatments in preventing bone mass loss around integrated implants.